Filosofi Ornamen Khas Tionghoa Restoran Kentjana Pecinan Bogor - Adhimas, Yogi Bagus; Wulandari, Catur; Fadia, Shinta Annisa (Waca Cipta Ruang, 2023)
This study aims to clarify why the design of the Kentjana Pecinan Bogor Restaurant has philosophical meaning embedded in the ornament display, in addition to aesthetic aspects. Furthermore, the placement of these decorations attempts to transform the Kentjana Pecinan Bogor Restaurant into a venue for cultural conversations in addition to serving traditional Chinese cuisine. The research method utilized to get this explanation is descriptive qualitative in order to gain optimal analysis. Field observations, interviews, documentation studies, and literature reviews were used to gather the majority of the study's data. Twelve ornaments total—five exterior and seven interior—were found as a consequence of the material investigation. Door god paintings, Pa Kua, small and huge lanterns, and dragon urns make up the external ornamentation. Photographs of Bogor City Heritage, typical Chinese woven plants: plum, orchid, bamboo, chrysanthemum (梅, 兰, 竹, and 菊), an altar of three gods (Earth God, Goddess Kwan Im, Cai Shen God, Meihua Flower Tree, Statues Mílè Púsà, and miniature Píxiū) were among the interior decorations discovered. This research includes the meanings and significance associated with each of these ornaments in their installation.